In vitro evaluation of the safety profile of cosmeceuticals containing growth factors and their analogues - Dieamant, Gustavo; Costa, Adilson; Bechelli, Liliana; Tibério, Juliana [UNESP]; Pereira, Carolina (My University, 2012)
Introduction: Aging skin is a condition that affects (or will affect) all people, and its treatment is considered a clinical challenge. Growth factors and their analogues are emerging as a promising therapeutic option. Objectives: To evaluate the safety profile of some dermocosmetic products with formulations based on growth factors - or their analogs intended for that purpose - using in vitro human skin cell culture models. Methods: Two types of cell cultures were studied, and the effects of the study products on the proliferation of melanoma cells and normal human fibroblasts were evaluated. Results: No significant morphological alterations were found in the cultured human melanoma, and no significant decrease in the number of healthy cells was verified in the normal fibroblasts culture. In some cases there was even a proliferation of those cells. Conclusions: These preliminary data demonstrate that cosmeceutical products containing growth factors as an active principle can be considered safe for topical application. © Sociedade Brasileira de Dermatologia.
Keywords: Intracellular signaling peptides and proteins; Skin; Skin aging